Tracing Triggers from Intern Islamic Conflict: Case Study of Syi’ah-Sunni in Indonesian - Ade Jamarudin; Asmal May (Ar-Raniry: International Journal of Islamic Studies, 2021)
Syi'ah is a group of Muslims who believe that sayyidina Ali ra. is a person who has the right to be a successor to the prophet, because the Prophet SAW. willed that his successor after death was sayidina Ali bin Abi Talib. The existence of new streams that emerge at this time is some of the other schools that are a challenge from the previous one too, from time to time and continue to always be there. Until now the above phenomenon cannot be avoided. Freedom of religion is an open choice for the community that leads to the progress of democracy. testament delivered by the Prophet Muhammad to "appoint Ali ibn Abi Talib to be caliph after the Prophet Muhammad. named after the hadith "Ghadir Khumm" used by the Shiites. Whoever violates this will be cursed by Allah and the Apostle. The religion brought by the prophet, until he died, was only one, namely Islam, not divided, Shi'a and Sunnah were not yet born. Furthermore, after the Prophet's death, it turns out there is a hadith or history that is considered by the Shiites as a will of the Prophet Muhammad. to the ummah to appoint Sayyidina Ali to the Caliph when he died. In terms of history, both believe there is a substitute for the Holy Prophet. namely the Shiite group, saidina Ali ra. minus three caliphs, while the sunnah saidina Ali ra. plus three other caliphs. According to Shi'a the appointment of Ali was based on revelation, while the appointment of the caliph according to the sunnah was through the ijtihad of Companions. Such understanding does not damage the joints of the faith in Islam, because they both adhere to the Qur'an and Sunnah. From a cultural point of view the Sunnah is culturally Shia. The proof is the existence of distinctive Shi'a traditions which are still being carried out by the sunnah; such as: the grave pilgrimage tradition, tahlilan, ark and so on. The tradition was born in the form of Shafi'i schools. So, outside of Syafi'i, inside Shi'a, or vice versa the tradition of Shi'a inside is sunnah.